IMPLEMENTASI NILAI-NILAI MULTIKULTURALPADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI KELAS X SEKOLAH USAHA PERIKANAN MENENGAH (SUPM) NEGERI PONTIANAKTAHUN PELAJARAN 2020-2021 - Bustami Bustami (CV. ADIBA AISHA AMIRA, 2023)
This research is motivated by a number of phenomena that occur in the Pontianak State Senior High School as a cadet school where all students are housed. Students' lives in this dormitory aside can strengthen their relationship, but differences in race, culture, religion and social status can also be a potential for disputes if not conditioned by religious tolerance and interfaith tolerance. The purpose of this study is to investigate and analyze the implementation of multicultural values in PAI learning in shaping the tolerance attitude of grade X students at the Pontianak State SUPM. This type of research used in this study is a mixed method that is a qualitative and quantitative approach. The subjects in this study were PAI teachers, principals and students. Data collection techniques used are indirect communication techniques, direct communication, non-participant observation and documentation techniques. Analysis of the data used is an interactive data analysis model through stages: data collection, data reduction, data display, verification and conclusion drawing. While quantitative data were analyzed through statistics using the SPSS Program. The data validity checking technique is triangulation and member checking. The results showed that: 1) The steps of implementing multicultural values in PAI learning in shaping student tolerance are carried out through four ways such as content integration by integrating various cultures and student group differences. The knowledge construction process by providing students with understanding of the cultural implications of tolerance. a, equity pedagogy presents the PAI learning process in accordance with differences and characteristics of students both in terms of race, culture or social strata of students. Prejudice reduction by identifying each difference, characteristics and background and the level of student needs. 2) Multicultural values contained in PAI learning in shaping student tolerance include democratic values, tolerance values, justice values, humanity values, pluralism values, peace values and inclusive values that are implemented through the PAI learning process which is integrated with material values others and contextual material development, through coaching after every morning prayer, involving students in social activities and through habituation. 3) Implications of the implementation of multicultural values on PAI learning in shaping the tolerance of students has a positive impact on schools, teachers, education personnel, students, families and also to the community.